2023
DOI: 10.1080/14786419.2023.2179624
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization, antioxidant activity, and cytotoxicity of fatty acids methyl esters from Handroanthus impetiginosus (Mart. ex DC.) Mattos (Bignoniaceae) seeds

Abstract: Handroanthus impetiginosus, popularly known as "ipê-roxo", is used in folk medicine to treat skin inflammations, infections, stomach diseases, and cancer. Fatty acid methyl esters (FAMEs) obtained from the esterification reaction of fatty acids (FA) found in the hexane extract (HE) of seeds of H. impetiginosus were identified by gas chromatography-mass spectrometry (GC-MS). The antioxidant and cytotoxic activities of the HE and FAMEs were evaluated. Methyl palmitate, methyl linoleate, methyl oleate, and methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Additionally, oleic acid has demonstrated antioxidant benefits and is well-known for its role in lowering the risk of ROS-induced pathologies and enhancing the immune system (Rydlewski et al, 2017 ). Recent studies further support the findings on the antioxidant and radical scavenging activity of FAs and FAME (Santos et al, 2024 ), while research confirms that B. pinnatum contains phytochemicals of pharmaceutical and pharmacological relevance (Mbachu et al, 2019 ).…”
Section: Resultsmentioning
confidence: 56%
“…Additionally, oleic acid has demonstrated antioxidant benefits and is well-known for its role in lowering the risk of ROS-induced pathologies and enhancing the immune system (Rydlewski et al, 2017 ). Recent studies further support the findings on the antioxidant and radical scavenging activity of FAs and FAME (Santos et al, 2024 ), while research confirms that B. pinnatum contains phytochemicals of pharmaceutical and pharmacological relevance (Mbachu et al, 2019 ).…”
Section: Resultsmentioning
confidence: 56%
“…These extracts may serve as natural sources of antioxidants based on their antioxidant activity [31,40,[49][50][51][52][53][54][55]. It was revealed that several bioactive compounds exist in this extract, including methyl oleate, isopropyl stearate, and 3,4-dihydroxy-1,6-bis-(3methoxy-phenyl)-hexa-2,4-diene-1,6-dione [54,[56][57][58]. There is evidence that such compounds contribute to the observed antimicrobial and antioxidant properties [31,50,[52][53][54][55].…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…Extracts from these plants showed significant antibacterial activity against Gram-positive bacteria, which is crucial given the rise in antibiotic resistance [14,[43][44][45][46][47][48]. These extracts may serve as natural sources of antioxidants based on their antioxidant activity [31,40,[49][50][51][52][53][54][55]. It was revealed that several bioactive compounds exist in this extract, including methyl oleate, isopropyl stearate, and 3,4-dihydroxy-1,6-bis-(3methoxy-phenyl)-hexa-2,4-diene-1,6-dione [54,[56][57][58].…”
Section: Molecular Docking Analysismentioning
confidence: 99%
See 1 more Smart Citation